The mediating effect of work-family conflict on the relationship between locus of control and job satisfaction - Ngah, Noryati; Ahmad, Aminah; Baba, Maznah (Science Publications, 2009)
Problem statement: Based on the literature review, few studies have tested the mediating effect of work-family conflict on the relationship between locus of control and job satisfaction. Approach: This study tested a mediation model consisting of job satisfaction as the dependent variable, locus of control as the independent variable and work-family conflict as the mediator. Data were gathered from 159 single mother employees, aged 45 and below and having at least one child, using self-administered questionnaires. The data were analyzed using correlation and multiple regression analyses. Results: Results of correlation analysis revealed that locus of control was related to work-family conflict and job satisfaction and work-family conflict was related to job satisfaction.Results of a series of multiple regression analyses indicated that work-family conflict partially mediates the relationship between locus of control and job satisfaction. During the screening process of potential recruits, employers should take into consideration locus of control as one of the important dispositional characteristics of candidates. Employers should look into the possibility of designing training programmes to assist employees in taking more control of events in their work situations. Conclusion: Single mother employees who believe that they are in control of the events that happen in their lives seem to be more satisfied with their jobs and seem to experience less work-family conflict.